2020
DOI: 10.7717/peerj.9256
|View full text |Cite
|
Sign up to set email alerts
|

Muscle activation varies between high-bar and low-bar back squat

Abstract: Background Differences in the muscular activity between the high-bar back squat (HBBS) and the low-bar back squat (LBBS) on the same representative group of experienced powerlifters are still scarcely investigated. The main purpose of the study was to compare the normalized bioelectrical activity and maximal angles within single homogeneous group between the HBBS and LBBS for 60% one repetition maximum (1RM), 65% 1RM and 70% 1RM. Methods Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…To increase the validity of the presented data and reduce the aforementioned confounding factors, all subjects were instructed to perform the squat using the same technique (same foot width, same foot angle, and same barbell position) as trained during the familiarization period. Recently, it was demonstrated that the position of the barbell highly affects thigh muscles activity, with high-bar squats eliciting greater involvement of the RF muscle compared to the low-bar position [ 24 , 25 ]. From a biomechanical perspective, this seems reasonable considering that high-bar squats are defined by a more upright torso, greater knee flexion, and less hip flexion compared to the low-bar variation, resulting in increased moment arm on the thigh muscles [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…To increase the validity of the presented data and reduce the aforementioned confounding factors, all subjects were instructed to perform the squat using the same technique (same foot width, same foot angle, and same barbell position) as trained during the familiarization period. Recently, it was demonstrated that the position of the barbell highly affects thigh muscles activity, with high-bar squats eliciting greater involvement of the RF muscle compared to the low-bar position [ 24 , 25 ]. From a biomechanical perspective, this seems reasonable considering that high-bar squats are defined by a more upright torso, greater knee flexion, and less hip flexion compared to the low-bar variation, resulting in increased moment arm on the thigh muscles [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, other authors 24 , 35 , 45 did not mentioned barbell placement during squats. Recently, it has been demonstrated that bar position highly affects activity of thigh muscles, where high-bar position provoke greater participation of RF during squat exercise, compare to the low-bar placement 46 . Hence, one could speculate that performing squat RT with a bar positioned at acromion level induce hypertrophy of all three vastii muscles and RF as well, and this should be investigated in further research.…”
Section: Discussionmentioning
confidence: 99%
“…High-bar squat training ( Murawa et al, 2020 ) at 25% 1RM was performed in the first, third, and fifth minutes of the session, and the rest was performed in the second and fourth minutes. The rhythm of the squat was controlled by a metronome 10 times/min (3 s concentric/3 s eccentric).…”
Section: Methodsmentioning
confidence: 99%